Digital transformation and knowledge management - Marchegiani, Lucia (Routledge, 2021)
"Knowledge capital is at the core of the socio-economic global system. Profit and not-for profit firms, institutions, and organizations, in general, face unique opportunities and threats related to knowledge management. Digital technologies and digital transformation offer a wide array of opportunities for value creation. At the same time, organizations need to foster newer, faster, and more dynamic ways of mobilizing and managing knowledge. Emerging trends, such as artificial intelligence, collective intelligence, agile methodologies, open innovation, and co-creation enable new business models and managerial paradigms that need to be understood and conceptualized. This book offers an extensive overview of the most recent trends in knowledge management and the most advanced theoretical approaches, while, at the same time, providing a wide array of case studies and evidence-based knowledge management practices. It takes into account the interrelation between ICT and knowledge management challenges, in terms of human/non-human interactions, which requires extraordinary organizational change and renewal. Further, the book presents an up-to-date examination of and guidance for the implementation of knowledge management in an era of unprecedented human/non-human interaction. The book conveys the results of more than a decade of research and applied experience in the field of knowledge management carried out by the author. It is intended not only for students and academics but also for managers and practitioners who are interested in deepening their understanding of knowledge and learning"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Knowledge management; Organizational learning; Information technology -- Management; Intellectual capital; Information society; Knowledge Management; Gestion des connaissances; Apprentissage organisationnel; Technologie de l'information; Gestion; Capital intellectuel; Société de l'information; BUSINESS & ECONOMICS / Knowledge Capital; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Information Management; Information technology; Management